Reading Etienne Leroux: a Libretto based on Seven Days at the Silbersteins and a Preface - Lucia, Christine (My University, 2007)
This Research Report comprises the preface to an opera libretto based on the English translation by Charles Eglington (1964) of Etienne Leroux’s novel Seven Days at the Silbersteins (1962), and the libretto itself. In the preface I discuss the genre of operatic libretto and the literary and personal context in which Leroux worked, by way of explaining why Seven Days made such a compelling challenge to adapt as libretto. I consider some of the issues involved in transposing a rambling allegorical narrative produced in Afrikaans in the 1960s in the lineage of the plaasroman, into a tighter postapartheid discourse in English in the 2000s, one that creates space for live music, singing, acting, staging, setting and pre-recorded audio-visuals – some of which take over the ‘layered’ significations of Leroux’s earlier literary discourse. A work of great poetic resonance in the original language (beautifully captured by poet and critic Charles Eglington in translation), this surrealist novel, so rooted in cultural and ideological tropes unique to Leroux’s time and yet presented by him as if they belonged to a timeless world, presents opportunities for a new kind of realisation as an operatic text in our own time.
Student Number : 0318162X - MA research report - School of Literature and Language Studies - Faculty of Humanities
Keywords: Libretto; Etienne Leroux; Opera; "Seven days at the Silbersteins; Novel; Sestigers